DEVELOPMENT OF STUDENTS' CRITICAL LITERACY WITHIN THE FOUR RESOURCES FRAMEWORK: THE USE OF QUESTIONS IN A TERTIARY EFL READING CLASS. - Endang setyaningsih, - (2018)
Despite the growing demand for critical literacy (CL) teaching, EFL classroom is still relatively resistant toward CL. This present study was designed to infuse critical literacy into tertiary EFL classroom and it highlighted the use of questions in the critical literacy teaching within the framework of Luke and Freebody's Four Resources. The framework and the use of questions were opted to minimize resistance and enhance doability, replicability and sustainability. The study was conducted for one semester and 35 first-year students of English Education were involved. Three foci were given emphasize: the students' critical literacy development, the immersion into CL of students with differing baseline, and retraction of success and failure on the use of questions in CL teaching within the framework. The instructions were roughly divided into introductory sessions and practice sessions. In both parts, there were reading sessions which were conducted in classby incorporating the SQ3R strategy into FRF and posing teacher's pre-developed questions based on the FRF in the teacher-led whole-class interaction and cooperative group arrangements. There were also writing sessions which were set as individual take-home assignments. To do the data collection, the study used multiple methods, namely participatory observation, test, artifact (students' works) analysis, interview and questionnaire. The data were analyzed interactively within the four resources framework and upon its completion of the data analyses, the data were triangulated.Quantitative data were computed using the non-parametric Wilcoxon Signed Rank Test. Four points of conclusion are withdrawn from the findings of the study. (1) The study bares that teacher's questions in CL instructions do not help students to improve their meaning making or general reading proficiency but aid them to move toward critical end of literacy.(2)The study confirms the fluidity of the roles within the FRF but at the same time questions the 'non-developmental' claim which is attached to the framework. (3) The study also concludes that students at diverging baselines address similar indicators of engagement in the roles but how they perform within each indicators differs. Two major factors that are identified to contribute to the difference are the material and the mode of tasks. (4) The CL teaching requires ample time to build the automated CL. Finally, (5) the FRF works as a framework but it does not provide clear teaching syntax.Incorporation of syntax as designed in this study is beneficial for both CL teaching and CL development. ;---Kelas pembelajaran bahasa Ingggris masih relatif imun terhadap pengajaran literasi kritis (LK) meskipun sangat kebutuhan dan tuntutan untuk pengajarannya sudah sangat mendesak. Penelitian ini dirancang untuk mengintegrasikan pengajaran LK ke dalam pembelajaran bahasa Inggris di tingkat universitas. Kajian ini mengedepankan penggunaan pertanyaan dalam pengajaran LK dalam kerangka Four Resources (FRF). Penggunaan pertanyaan dan kerangka FRF dipilih karena keduanya dapat meminimalisir penolakan sekaligus meningkatkan keberlanjutan serta replikabilitas penelitian. Penelitian ini berlangsung selama satu semester dengan melibatkan 35 mahasiswa semester satu sebagai peserta. Penelitian berfokus pada tiga hal: perkembangan literasi kritis mahasiswa, imersi ke dalam LK oleh mahasiswa dengan kemampuan dasar yang berbeda, dan retraksi keberhasilan dan kegagalan penggunaan pertanyaan dalam pengajaran LK dengan FRF. Pengajaran LK dalam penelitian ini pada dasarnya dibagi dalam dua bagian: sesi introduction dan sesi latihan. Pada kedua bagian, terdapat sesi reading yang dilaksanakan dalam kelas dengan mengintegrasikan strategi SQ3R dalam FRF, dan sesi Writing yang dilaksanakan di luar kelas sebagai tugas individu. Pada sesi Reading terdapat dua kegiatan utama. Pertama, diskusi kelas yang dipimpin guru dan membahas pertanyaan berbasis FRF yang telah disiapkan oleh dari guru. Kedua, kerja kelompok secara 'cooperative' yang membahas pertanyaan berbasis FRF yang disusun oleh siswa. Untuk pengumpulan data, penelitian ini menggunakan beragam metode yaitu observasi berperan aktif, tes, analisis artifak/ tugas mahasiswa, wawancara, dan kuisioner. Data yang diperoleh dianalisis secara interaktif dalam FRF untuk kemudian ditrianggulasi. Data kuantitaif dikomputasi dengan menggunakan tes non-parametric Wilcoxon Signed Rank Test. Berdasar hasil temuan penelitian, diperoleh empat poin simpulan. (1) Pertanyaan dari guru tidak membantu siswa untuk memahami bacaan tapi dapat membantu siswa bergerak ke dari literasi konvensional ke arah literasi kritis. (2) Studi ini mengkonfirmasi 'fluidity' peran pembaca namun pada saat yang sama mempertanyakan nosi 'non-developmental' yang disematkan pada FRF. (3) Siswa dengan kemampuan dasar beragam menunjukkan indikasi yang sama dalam keterlibatan mereka pada suatu peran, namun demikian, performa dalam tiap indikasi menunjukkan perbedaan. Dua factor utama yang berperan dalam adanya perbedaan adalah materi dan mode tugas. (4) pengajaran LK memerlukan waktu yang memadai untuk pembentukan otomatisasi LK. (5) FRF berperan sebagai kerangka pengajaran namun tidak menyediakan langkah yang jelas dalam implementasi. Integrasi langkah pembelajaran ke dalam FRF seperti yang dirancang dalam kajian ini memnguntungkan tidak saja bagi pembelajaran LK tetapi juga bagi perkembangan LK siswa.